2015
DOI: 10.1002/polb.23754
|View full text |Cite
|
Sign up to set email alerts
|

Secondary doping in poly(3,4‐ethylenedioxythiophene):Poly(4‐styrenesulfonate) thin films

Abstract: The electrical and structural properties of poly (3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) thin films deposited from aqueous dispersion using different concentrations of selected secondary dopants are studied in detail. An improvement of the electrical conductivity by three orders of magnitude is achieved for dimethyl sulfoxide, sorbitol, ethylene glycol, and N,N-dimethylformamide, and the secondary dopant concentration dependence of the conductivity exhibits almost identical behavior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 39 publications
8
79
0
Order By: Relevance
“…It has been reported that the addition of different dopants to an aqueous solution of PEDOT/PSS produces an enhancement in the conductivity of PEDOT/PSS films obtained from the solution [2930]. In our case, the additives were deposited as a thin film on the top of the PEDOT/PSS layer and the same effect was observed.…”
Section: Resultssupporting
confidence: 70%
“…It has been reported that the addition of different dopants to an aqueous solution of PEDOT/PSS produces an enhancement in the conductivity of PEDOT/PSS films obtained from the solution [2930]. In our case, the additives were deposited as a thin film on the top of the PEDOT/PSS layer and the same effect was observed.…”
Section: Resultssupporting
confidence: 70%
“…However, this conductivity is less than recently reported highly conductive PEDOT‐based films: crystalline PEDOT films (5000 S cm −1 ) and structurally optimized “metallic” PEDOT/PSS thick films (700 S cm −1 ), for example. Though the PEDOT was assumed to occupy the whole area of HNL in the above estimation, the PEDOT volume should be much less than the assumption due to following two reasons.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, the microscopic optimizations adopted in the studies mentioned above have not been carried out in this study. Hence, we think that the PSS‐free PEDOT developed in this work is still open to conductivity improvement.…”
Section: Resultsmentioning
confidence: 99%
“…[11] The process often involves adding a high boiling point organic solvent, such as sorbitol or dimethyl sulfoxide, to the PEDOT:PSS emulsion before processing thin films followed by thermal annealing. [12] Alternatively, the polymer film can be immersed in the high boiling point solvent. Although the mechanism of the increase in conductivity is not fully understood, most evidence points to a morphological change.…”
Section: Pedotmentioning
confidence: 99%